2016
DOI: 10.1103/physrevd.94.063507
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to cosmic reionization from dark matter annihilation and decay

Abstract: Dark matter annihilation or decay could have a significant impact on the ionization and thermal history of the universe. In this paper, we study the potential contribution of dark matter annihilation (s-wave-or p-wave-dominated) or decay to cosmic reionization, via the production of electrons, positrons and photons. We map out the possible perturbations to the ionization and thermal histories of the universe due to dark matter processes, over a broad range of velocity-averaged annihilation cross-sections/decay… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
232
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(246 citation statements)
references
References 132 publications
(231 reference statements)
12
232
2
Order By: Relevance
“…Here we neglect structure formation; previous studies of the impact of DM annihilation on the CMB anisotropy spectrum have demonstrated that most of the effect arises from high redshifts, z ∼ 600, where inhomogeneities in the DM density are small [21,27]. Energy injection from DM annihilations and decays extending until late time, and the possible impact on reionization is studied in [28][29][30].…”
Section: Energy Injection From Dark Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…Here we neglect structure formation; previous studies of the impact of DM annihilation on the CMB anisotropy spectrum have demonstrated that most of the effect arises from high redshifts, z ∼ 600, where inhomogeneities in the DM density are small [21,27]. Energy injection from DM annihilations and decays extending until late time, and the possible impact on reionization is studied in [28][29][30].…”
Section: Energy Injection From Dark Mattermentioning
confidence: 99%
“…For models at the limits of the bounds we will present, the modification to the hydrogen ionization fraction x e can be as large as ∆x e ∼ 10% just prior to reionization, which is sufficient to non-trivially modify the fraction of deposited power proceeding into ionization (vs heating or excitation) for low-energy electrons [18]. However, a model with even shorter decay time / larger power injection was considered in [29], and it was shown in that case that the overall change to the ionization history from accounting for these backreaction effects was very small. Furthermore, we expect the CMB constraint from decaying DM with a long lifetime to arise mostly from higher redshifts, z ∼ 300 [21], as we will discuss in more depth in the next section.…”
Section: Energy Injection From Dark Mattermentioning
confidence: 99%
“…This remains true in the 5-D extensions of these models that we consider. These constraints essentially place bounds on the DM annihilation cross section into various electromagnetically interacting final states that can lead to re-ionization in the early universe with the sensitivity peaking near z ∼ 600 [54,55]. For example, for 50-100 MeV DM that has an s-wave annihilation into the e + e − final state (which we might expect to be the dominant mode in this mass range), the annihilation cross-section is constrained to roughly satisfy the bound < σv > (1 − 3) · 10 −29 cm 3 s −1 This is ∼ 3 orders of magnitude smaller than the canonical thermal cross section needed at freeze-out to achieve the observed relic density [56], i.e., < σv > 4.5 · 10 −26 cm 3 s −1 for (self-conjugate) DM in this mass range.…”
Section: Cosmology: Planck and Cmb Constraintsmentioning
confidence: 99%
“…Given that constraints from CMB for p-wave annihilation are both weak and model-dependent, and that, moreover, the corresponding detectability of a gamma-ray signal is highly dependent on the velocity distribution in the target dark matter halo, in this work we exclusively focus on s-wave annihilators. Limits on p-wave annihilating dark matter from CMB for larger dark matter masses in standard WIMP scenarios have been presented in [39,43,44].…”
Section: Thermal History and Cmb Constraintsmentioning
confidence: 99%
“…Equation (10) results in a suppression on the energy injection and thus will not alter the thermal history until low redshift. At the redshifts where dark matter contributes one must also consider the clumping effect due to the formation of dark matter halos [39]. In addition, to compute the z ref one must know the temperature of kinetic decoupling (T kd ), which is model dependent (see e.g.…”
Section: Thermal History and Cmb Constraintsmentioning
confidence: 99%